External Soft-Tissue Hemostatic Clamp Compared to a Compression Tourniquet as Primary Hemorrhage Control Device in Pilot Flow Model Study. Issue 2 (27th March 2019) - Paquette, Roland; Bierle, Ryan; Wampler, David; Allen, Paul; Cooley, Craig; Ramos, Rosemarie; Michalek, Joel; Gerhardt, Robert T.
Abstract : Introduction: Acute blood loss represents a leading cause of death in both civilian and battlefield trauma, despite the prioritization of massive hemorrhage control by well-adopted trauma guidelines. Current Tactical Combat Casualty Care (TCCC) and Tactical Emergency Casualty Care (TECC) guidelines recommend the application of a tourniquet to treat life-threatening extremity hemorrhages. While extremely effective at controlling blood loss, the proper application of a tourniquet is associated with severe pain and could lead to transient loss of limb function impeding the ability to self-extricate or effectively employ weapons systems. As a potential alternative, Innovative Trauma Care (San Antonio, Texas USA) has developed an external soft-tissue hemostatic clamp that could potentially provide effective hemorrhage control without the aforementioned complications and loss of limb function. Thus, this study sought to investigate the effectiveness of blood loss control by an external soft-tissue hemostatic clamp versus a compression tourniquet. Hypothesis: The external soft-tissue hemostatic clamp would be non-inferior at controlling intravascular fluid loss after damage to the femoral and popliteal arteries in a normotensive, coagulopathic, cadaveric lower-extremity flow model using an inert blood analogue, as compared to a compression tourniquet. Methods: Using a fresh cadaveric model with simulated vascular flow, this study sought to compare the effectiveness of the external soft-tissue hemostatic clamp versus the compression tourniquet to control fluid loss in simulated trauma resulting in femoral and posterior tibial artery lacerations using a coagulopathic, normotensive, cadaveric-extremity flow model. A sample of 16 fresh, un-embalmed, human cadaver lower extremities was used in this randomized, balanced two-treatment, two-period, two-sequence, crossover design. Statistical significance of the treatment comparisons was assessed with paired t-tests. Results were expressed as the mean and standard deviation (SD). Results: Mean intravascular fluid loss was increased from simulated arterial wounds with the external soft-tissue hemostatic clamp as compared to the compression tourniquet at the lower leg (119.8mL versus 15.9mL; P <.001) and in the thigh (103.1mL versus 5.2mL; P <.001). Conclusion: In this hemorrhagic, coagulopathic, cadaveric-extremity experimental flow model, the use of the external soft-tissue hemostatic clamp as a hasty hemostatic adjunct was associated with statistically significant greater fluid loss than with the use of the compression tourniquet. Paquette R, Bierle R, Wampler D, Allen P, Cooley C, Ramos R, Michalek J, Gerhardt RT. External soft-tissue hemostatic clamp compared to a compression tourniquet as primary hemorrhage control device in pilot flow model study. Prehosp Disaster Med . 2019;34(2):175–181